Spread, scale-up, and sustainability of video consulting in health care: Systematic Review and synthesis guided by the NASSS framework - James, HM; Papoutsi, C; Wherton, J; Greenhalgh, T; Shaw, SE (JMIR Publications, 2021)
Background: COVID-19 has thrust video consulting into the limelight, as health care practitioners worldwide shift to delivering care remotely. Evidence suggests that video consulting is acceptable, safe, and effective in selected conditions and settings. However, research to date has mostly focused on initial adoption, with limited consideration of how video consulting can be mainstreamed and sustained.